STRATEGI MARIJUANA POLICY PROJECT DALAM MENDORONG OPINI PUBLIK TERHADAP PENERIMAAN LEGALISASI GANJA DI COLORADO - Purnamasari, Ika Ayu; Fasisaka, Idin; Prameswari, Anak Agung Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 2 (2019), 2019)
ABSTRACT Marijuana legalization is a form of public policy that most raises pros and cons in Colorado, United States. The United States Federal Law which classified marijuana as illegal drugs causes millions of people to be arrested and prosecuted with heavy fines even though they have a small amounts of marijuana. The Marijuana Policy Project (MPP) as the largest Non Government Organization (NGO) for marijuana reform in the United States feels the need to reform the legalization policy of marijuana in the state that has a long history of marijuana use, Colorado. This study aims to describe the influence of the Marijuana Policy Project as an interest group towards the forming of public opinion and the process of public policy making in Colorado. This study assesed by using public opinion and influence of interest groups concepts within 2011-2014 as timeline.   Keyword: marijuana legalization, interest group, influence, public opinion